2017
DOI: 10.1001/jamapsychiatry.2017.2573
|View full text |Cite
|
Sign up to set email alerts
|

Association of White Matter Structure With Autism Spectrum Disorder and Attention-Deficit/Hyperactivity Disorder

Abstract: Dimensional analyses provided a more complete picture of associations between ASD traits and inattention and indexes of white matter organization, particularly in the corpus callosum. This transdiagnostic approach can reveal dimensional relationships linking white matter structure to neurodevelopmental symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
127
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 70 publications
(142 reference statements)
12
127
1
1
Order By: Relevance
“…Others have also reported on the absence of clear biological distinctions on structural or functional neuroimaging measures when comparing different NDD diagnostic groups [13][14][15][16][17][18] Data-driven clustering approaches offer a methodological alternative to conventional comparisons between clinically defined groups. This alternative approach may better disentangle heterogeneity within and across current diagnostic categories to identify participant subgroups that may be more similar to each other in brain or behavior [10].…”
Section: Introductionmentioning
confidence: 99%
“…Others have also reported on the absence of clear biological distinctions on structural or functional neuroimaging measures when comparing different NDD diagnostic groups [13][14][15][16][17][18] Data-driven clustering approaches offer a methodological alternative to conventional comparisons between clinically defined groups. This alternative approach may better disentangle heterogeneity within and across current diagnostic categories to identify participant subgroups that may be more similar to each other in brain or behavior [10].…”
Section: Introductionmentioning
confidence: 99%
“…Approaches differ in how heterogeneity is decomposed, from utilizing theoretical a priori known stratifiers 21,22 or dimensions, to completely data-driven approaches 12,[23][24][25] . Models for understanding heterogeneity also differ considerably, with some conceptualizing distinctions as categorical/qualitative, continuous/dimensional, and/or where distinctions or similarities may cut across diagnostic boundaries [25][26][27] . Work can also differ with regards to aims that are specific to understanding heterogeneity within one level of analysis 28, 29 , while others attempt to extend models to explain heterogeneity across levels [30][31][32][33][34][35] .The purpose of this paper is not to provide an in-depth review of the literature on these areas.…”
mentioning
confidence: 99%
“…Neuroimaging studies contrasting either ASD or ADHD against typically developing people (TD) have shown that both disorders are characterized by abnormal connectivity in function as well as structure (reviewed in (Anagnostou and Taylor 2011, Aoki et al 2013a, Castellanos and Aoki 2016, Aoki et al 2018)). Thus, some prior studies using diffusion tensor imaging (DTI) have enrolled the three groups (ASD, ADHD, and TD) and reported on similarities and distinctions in white matter between the disorders compared with TD (Ameis et al 2016, Aoki et al 2017, Chiang et al 2017). Results of categorical analyses contrasting the three diagnostic groups vary, possibly because of heterogeneity of the developmental disorders (Pelphrey et al 2011, Ecker and Murphy 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Results of categorical analyses contrasting the three diagnostic groups vary, possibly because of heterogeneity of the developmental disorders (Pelphrey et al 2011, Ecker and Murphy 2014). However, they consistently emphasize the corpus callosum (Ameis et al 2016, Aoki et al 2017, Chiang et al 2017). Besides categorical analysis, dimensional analyses were also conducted in these studies in which all the participants were allocated to one group and the relationship between DTI parameters and ASD symptoms was examined.…”
Section: Introductionmentioning
confidence: 99%